Does Anticonvulsant Treatment Influence Pain Perception in Epileptic Children? - Ferrara, Pietro; Bottaro, Giorgia; Angeletti, Silvia; Ianniello, Francesca; Romano, Valerio; del Bufalo, Francesca; Chiaretti, Antonio; Battaglia, Domenica; Dicuonzo, Giordano (Neuropediatrics, 2013)
Background The aims of our study were to evaluate pain perception in epileptic children and to establish the influence of anticonvulsant drugs on pain perception. Methods The study involved 40 children, 30 with epilepsy and 10 healthy control subjects. In the group of epileptic children, 10 were not treated and 20 assumed a single drug. From all children of each group, one sample of saliva was collected through a noninvasive device 15 minutes before (t0), during (t1), and 15 minutes after (t2) blood withdrawal, and salivary α-amylase activity was then determined. Results No statistically significant difference was found at t0 and at t1, indicating that in both groups venipuncture equally induced a state of stress. Conversely, at t2 a statistically significant difference (p = 0.0195) was found, suggesting that epileptic children presented a greater sensitization to pain and a slower recovery from stress. Comparing furthermore data obtained in children with epilepsy not treated with those registered in treated ones, we found a statistically significant difference at t0 (p = 0.012), at t1 (p = 0.037), and at t2 (p = 0.011). Conclusions Anticonvulsant drugs do not seem to influence pain perception and enzymatic activity levels in epileptic patients.
Keywords: anticonvulsant; pain; children; epileptic; amylase